Management of high-output cardiac failure caused by head and neck AVMs: Percutaneous suture-assisted ethanol and coil embolotherapy - Wen, Ming-zhe; Li, Xin-yu; Shen, Yu-chen; Wang, Zhen-feng; Zheng, Lian-zhou; Wang, De-ming; Fan, Xin-dong; Su, Li-xin; Yang, Xi-tao (Frontiers in Cardiovascular Medicine, 2022)
Abstract Purpose: The aim of this study is to describe the treatment technique, outcomes and complications of Schrödinger stage Ⅳ head and neck arteriovenous malformations (HNAVMs) with associated high-output cardiac failure (HOCF) using ethanol and coils with the percutaneous suture technique. Methods: From January 2015 to December 2019, nineteen patients who had HNAVMs with associated HOCF treated first with percutaneous suture of the dilated drainage vein (DDV) and subsequent embolization with coils and ethanol. The percutaneous suture of DDV was preferred to be performed, followed by deployment of coils and the injection of absolute ethanol via transarerial approach, transvenous approach, direct puncture approach or both of them. Treatment outcomes, complication rates were evaluated on follow-up. Results: Nineteen patients who experienced HNAVMS with HOHF had a dilated drainage vein. These patients received 19 percutaneous suture procedures, 84 embolization procedures with ethanol and coils. Complete or >90% closure of the AVM was achieved in all patients. 19 patients with > NYHA stageⅡimproved to stageⅠ, and symptom of dyspnea disappeared after embolization. 19 patients (100%) presented with cardiac functional impairment were cured. Symptom of five patients with bleeding disappeared. All patients presented with cosmetic concerns; ten were cured and eight experienced a clearly recognizable improvement. 19 patients (100%) presented with impairment in daily life which was resolve. Five minor complications were encountered and recovered by the self. No major complications occurred. Conclusion: This study provides evidence that ethanol and coil embolotherapy is effective and safe in treating HOHC caused by HNAVMs with acceptable complications in these cases. Percutaneous suture technique for DDV management can act as an adjunct for embolotherapy.